Desenvolvimento de uma metodologia para restauração automática de redes de distribuição - Vargas Peralta, Renzo Amilcar [UNESP] (2015)
This work proposes a methodology based in the meta-heuristic tabu search to distribution power system restoration considering distributed generators installed on the system, using the encoding system node depth representation. The problem is established as a mixed-integer nonlinear programming taking into account the mainly goals: to minimize both the number of consumers without supply and the number of switching. This work also proposes a logic sequence of switching operations, taking care of operational issues. The proposed algorithm was implemented in C++ programming language and tested in a 136 and a 7052 bus distribution systems